Pengaruh Konten Pameran Virtual 'My Life As VCDears' Terhadap Citra Prodi VCD - Quina Reivaldi Limantara (ULTIMART Jurnal Komunikasi Visual, 2022)
Abstract: Visual Communication Design (VCD) has a vision of creating graduates who are able to produce designs that are unique and acceptable to society. Students are encouraged to always do self-exploration. This time, the Graphic On Product (GOP) course held a collage art exhibition with the title My Life As VCDears, where students were given the opportunity to tell their experiences while on VCD without any intervention from the lecturer or tutor. This study uses descriptive analysis based on the results of source exploration. Twenty (20) student works became the research subjects and the My Life As VCDears exhibition became the object of research. The result is that 8 out of 20 student works (40%) show a positive impression, 2 out of 20 student works (10%) show both sides, and 10 out of 20 student works (50%) show a negative impression about life on VCD. This will greatly affect the interpretation and reaction stages. Further research can continue this research in order to gain full insight. However, it is possible that there will be misperceptions, especially due to errors in attention, because not all visitors are willing to understand 100% of the works on display.